Visceral adipose tissue macrophage-targeted TACE silencing to treat obesity-induced type 2 diabetes. (December 2017) - Yong, Seok-Beom; Song, Yoonsung; Kim, Yong-Hee
Abstract: Obesity is an increasingly prevalent global health problem. Due to its close relations with metabolic diseases and cancer, new therapeutic approaches for treating obesity and obesity-induced metabolic diseases are required. Visceral white adipose tissue (WAT) has been closely associated with obesity-induced inflammation and adipose tissue macrophages (ATMs) are responsible for obesity-induced inflammation by releasing inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6. TNF-α converting enzyme (TACE) is a transmembrane enzyme that induces the enzymatic cleavage and release of inflammatory cytokines. In this study, we developed a nonviral gene delivery system consisting of an oligopeptide (ATS-9R) that can selectively target visceral ATMs. In here we shows visceral adipose tissue-dominant inflammatory gene over-expressions in obese mouse and our strategy enabled the preferential delivery of therapeutic genes to visceral ATMs and successfully achieved ATM-targeted gene silencing. Finally, ATS-9R-mediated TACE gene silencing in visceral ATMs alleviated visceral fat inflammation and improved type 2 diabetes by reducing whole body inflammation.